Denying to the grave : why we ignore the facts that will save us - Gorman, Sara E.; Gorman, Jack M. (Oxford University Press, 2017)
Why do some parents refuse to vaccinate their children? Why do some keep guns at home, despite scientific evidence of risk to their family members? And why do people use antibiotics for illnesses they can't possibly alleviate? When it comes to health, many people insist that science is wrong, that the evidence is incomplete or inconclusive, and that unidentified hazards lurk everywhere to harm us.